User-Centered Design Approach for a Mobile Travel App: UI/UX Case Study of Ciletuh-Palabuhanratu Geopark - Muhammad Rizky Yusril Arasyhi; Muhamad Muslih (Teknika, 2025)
This study presents the design of a mobile travel application named Explore, aimed at enhancing the tourism experience in the Ciletuh-Palabuhanratu Geopark, West Java, Indonesia. Using a User-Centered Design approach, the process followed four stages: Context Analysis, Defining Requirements, Design, and Evaluation. Key features include an AI-powered assistant chatbot, real-time crowd updates, ticketing, and intuitive navigation. The design evolved from wireframes to high-fidelity prototypes tailored for mobile use. Usability testing with fifteen participants using the System Usability Scale resulted in an average score of 81.5, indicating high user satisfaction and effective functionality. This application not only complements the existing Geopark website by offering a more interactive and functional platform but also improves access to tourism information for visitors. Additionally, it supports local economic growth by encouraging increased activity in nearby sectors such as culinary services, accommodations, and transportation. The findings highlight that integrating user feedback and AI-based features can significantly enhance user experience in digital tourism platforms.